Una nueva especie de Atelopus A.M.C. Dumeril & Bibron 1841 (Amphibia: Bulonidae) de la cordillera Occidental, Colombia - Ruiz Carranza Pedro M.; Vélez Claudia María; Ardila Robayo María Cristina (Caldasia)
A new species of the genus Atelopus of the longirostris Group (A.negreti) is nomined and described from the Eastern slope of the Cordillera Occidental, S. P.N.N. Munchique, Cauca, at 1470-1580m. Se nomina y describe una nueva especie de atelopus del grupo longirostris: A.negreti del flanco occidental de la Cordillera Occidental, límite S. del Parque Nacional Natural Munchique, Cauca, 1470-1580m.